Audit firm retention : analysing the effect of audit quality and the mediating role of customer satisfaction - Zubaidah Mohd Ali (2020)
Audit firm retention is a reliable indicator for audit firms to measure their competitive advantage for firm survival. To sustain audit firm retention, high audit qualities are crucial. Thus, it is important for the audit firm to deliver audit related services up to the expectation of the client firm. Apart from audit quality, client satisfaction is also considered an important element in deciding whether to retain or replace the existing audit firm. In view of this, based on the social exchange theory, the study aims to explore the relationship between audit quality and audit firm retention, with the mediation effect of satisfaction among Small and Medium Enterprises (SMEs) particularly in Sabah, Malaysia. The study employed a quantitative research method. Two hundred and fifty questionnaires were distributed to the SMEs. However, only 95 answered questionnaires were useable, yielding a response rate of 38%. The study deployed Statistical Package for Social Sciences (SPSS) version 21 and SmartPLS version 3.0 to conduct descriptive and statistical analysis. The findings indicate that SMEs’ decision to retain their existing audit firm depends on service quality provided by the audit firm. In addition, when the study put forward satisfaction to mediate the relationship between audit quality and audit firm retention, it was revealed that satisfaction has a mediation effect on clients’ satisfaction towards audit firm retention through competency and service quality. This study is significant as it is very insightful and provides a comparable study in Sabah which is hardly available. In addition, this study helps in gaining an understanding of the perceptions of audit quality and client satisfaction in order to create more effective retention strategies based on empirical evidence.